Impact of teacher’s interaction pattern for seventh grade student - Khumayda Shofiyul Khaliyah; Dzul Rachman (Journal of English Language and Pedagogy, 2019)
Classroom interaction is essential for English foreign language student. Additionally, discourse analysis is the examination of the language used by members of a speech community. The objectives of this study to describe the pattern of teacher-student interaction used by the teacher in the classroom at MTs Nurul Ummah Yogyakarta and to reveal the impact of teacher-student interaction pattern to the student contribution on the MTs Nurul Ummah Yogyakarta. This research employed discourse analysis. Includes English teacher and seventh-grade students of MTs Nurul Ummah Yogyakarta as the participants. Data were collected through observation and recording. The collected data were analysed by Walsh using discourse analysis. Findings show there are 30 patterns in 18 exchanges of teacher-student interaction in the classroom. The type of designs are: IR, IRE, IRRE, IRRF, IRREIRE, IRRRE, IRF, IRFRRRERE, IRR, IRRRRRRE, IRRFRE, IRI, IRRRRRE, IIIII, IIRE, IRFRE, IIRE, IIIR, IIR, IEIRRI, IRFR, IRRRRRRRRRRRRE, IRRRRRRRER, IEI, IRRRRF, IIIIRRF, IIIIRR, IRRII, IRFII, IREI. The impacts of the type interaction pattern to the student contribution are: student can repeat the teacher initiation, a student could express their idea, a student could ask the question on the teacher explanation, student response appropriate for teacher talk.